2019
DOI: 10.1017/jns.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Dietary choline supplementation attenuated high-fat diet-induced inflammation through regulation of lipid metabolism and suppression of NFκB activation in juvenile black seabream (Acanthopagrus schlegelii)

Abstract: The present study aimed to investigate whether dietary choline can regulate lipid metabolism and suppress NFκB activation and, consequently, attenuate inflammation induced by a high-fat diet in black sea bream (Acanthopagrus schlegelii). An 8-week feeding trial was conducted on fish with an initial weight of 8·16 ± 0·01 g. Five diets were formulated: control, low-fat diet (11 %); HFD, high-fat diet (17 %); and HFD supplemented with graded levels of choline (3, 6 or 12 g/kg) termed HFD + C1, HFD + C2 and HFD + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…This inflammatory response was slightly alleviated by consuming more choline and removing the choline synthesis inhibitor, AMP. As mentioned earlier, choline supplementation has been demonstrated to attenuate pro-inflammatory response in juvenile black seabream intestine and liver by down-regulating nfb and tnf mRNA expressions (31) . This might be the case for juvenile YTK fed a choline-deficient diet.…”
Section: Liver Histologymentioning
confidence: 84%
See 1 more Smart Citation
“…This inflammatory response was slightly alleviated by consuming more choline and removing the choline synthesis inhibitor, AMP. As mentioned earlier, choline supplementation has been demonstrated to attenuate pro-inflammatory response in juvenile black seabream intestine and liver by down-regulating nfb and tnf mRNA expressions (31) . This might be the case for juvenile YTK fed a choline-deficient diet.…”
Section: Liver Histologymentioning
confidence: 84%
“…For example, supplementing choline to a high-lipid diet was reported to reduce liver lipid content, cell damage, and inflammatory response (i.e. down-regulate NFκB expression) in juvenile black seabream (Acanthopagrus schlegelii) (31) . Choline supplementation also prevented signs of lipid malabsorption syndrome in post-smolt Atlantic salmon (Salmo salar L.) but had little effect on liver lipid metabolism (44) .…”
Section: Introductionmentioning
confidence: 99%
“…Srebp-1 is a transcription factor responsible for regulating cholesterol and fatty acid/lipid biosynthesis pathways (54,57) . Fas is involved in de novo fatty acid synthesis (28) . G6pd and 6pgd participate in NADPH production and are important genes for fatty acids biosynthesis (58) .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (1) reported that black sea bream is prone to store lipid in their liver. Previous studies in black sea bream reported that L-carnitine (27) , choline (28) and bile acids (10) supplementation could improve immune and antioxidative abilities and reduce the histopathological changes caused by HL diets. The present study aimed to investigate whether BBR supplementation in HL diet could effectively reduce lipid accumulation in the liver of black sea bream.…”
mentioning
confidence: 96%
“…145 In juvenile black seabream, choline supplementation suppressed NF-κB activation and increased the expression of lipolysis pathway genes. 146 The increased uptake of choline by HCCs cells promotes phospholipid formation, DNA hypermethylation, and hepatocyte proliferation. Gougelet et al showed that choline-deficient diet reverses these effects and promotes regression of HCC that overexpress β-catenin in mice.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 99%